A Review of Seaport Microgrids for Green Maritime Transportation: The Shore and the Seaside - Almansor, Mohammed Jamal; Din, Norashidah Md; Baharuddin, Mohd Zafri; Alsayednoor, Huda Mohammed; Al-Shareeda, Mahmood A.; Ma, Maode; Ramly, Athirah Mohd (Universitas Muhammadiyah Yogyakarta, 2024)
Emerging from the field of microgrids is an efficient and persuasive transitional technology with great promise for easing energy crises, environmental worries, and economic limitations in seaports. When it comes to high-performance ports, this technology becomes even more important. One example is smart ports, which use state-of-the-art ICT applications to completely revamp container and vessel management. Strengthening national economic sustainability and global competitiveness are both impacted by this invention. Reducing the environmental impact of the maritime transport business is no easy feat. In this study, we take a look at how seaport microgrids are becoming more important in the quest for environmentally friendly marine transportation. We take a look at the major problems that contemporary seaports are facing, such as the ever-increasing need for energy, the contamination of both the air and water from ship emissions and the unpredictable cost of electricity. The goal is to bring together current information about smarter ports by giving examples and to encourage new ideas and research in this field. As part of our efforts to inspire new research into smart port development, we also outline certain open questions that need answering. This report could serve as a valuable resource for future research on seaport microgrids.